Down the banking hole - Premrl, Peter; Dobovšek, Bojan; Slak, Boštjan (Intersections. East European Journal of Society and Politics, 2024)
Purpose The aim of the paper was to analyze who was responsible for the deterioration of the Slovenian banking sector to the degree, that the 2008 financial crisis almost destroyed the sector and international bailout was on the horizon. Design/methodology/approach Literature review, where a specific focus was given to reports from law enforcement agencies and commissions investigating banking practices, were deepened with a qualitative empirical study. To gain insight into the reasons why this situation unfolded, ten structured interviews were done, and interviewees included experts with experience in the fields of prevention, detection, investigation and prosecution of economic crime, bad credit management, central banking, parliamentary committee management, forensic investigations, investigative journalism, and experts with academic knowledge in law and economics. Findings Five different investigations looked into the behaviour of banking sector actors pre-, mid-, and after the 2008 financial crisis. They found that behaviours ranged from negligence to criminal acts. And the findings from the interviews show that the perpetrators were people of high social status with great social influence, which is why people are often not willing to testify against them. The main reason on the detection and prosecution side, however, was criminal investigators, prosecutors, judges, and others had fears of retaliation from their superiors, losing their jobs and raising their heads above the parapets and being publicly lambasted in the media. Originality This study is the only one that has so far provided an insight in the issues of deterioration of Slovenian banking sector from the criminological and criminal investigative standpoint. Keywords: Financial crime, Banking sector, Investigation, White-collar crime